Object-oriented programming in FEM and BEM: a bibliography (1990–2003) - Mackerle, Jaroslav (Advances in engineering software (1992), 2004)
This paper gives a bibliographical review of the object-oriented programming applied to the finite element method as well as to the boundary element method. The bibliography at the end of the paper contains references to papers, conference proceedings and theses/dissertations on the subject that were published between 1990 and 2003. The following topics are included: finite element method—object-oriented programming philosophy, mesh modelling, distributed/parallel processing, toolkits and libraries, object-oriented specific applications (aerospace, civil engineering/geomechanics, coupled problems, dynamical systems, electromagnetics, fracture mechanics and contact problems, material simulations/manufacturing, mechanical engineering, nonlinear structural simulations, optimization, others); boundary element method. Totally 408 references are listed.